2019
DOI: 10.1097/mol.0000000000000645
|View full text |Cite
|
Sign up to set email alerts
|

Implications of serial coronary computed tomography angiography in the evaluation of coronary plaque progression

Abstract: Purpose of review The purpose is to review the use of coronary computed tomography (CT) angiography to assess coronary plaque burden/progression and to discuss about recent clinical trials that have utilized this imaging modality to study the effect of new pharmacotherapies on plaque burden/progression. Recent findings There are numerous clinical trials that have utilized coronary CT angiography to demonstrate the potential benefits of statins, apixaban, rivaroxaban, aged garlic extract, biologic agents, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The clinical management was adjusted in 66% of the entire study population demonstrating the high potential of coronary CTA examinations for therapy evaluation and optimization in CAD patients. Hence, coronary CTA is expected to be increasingly utilized to track CAD progression ( 34 ). In our opinion, prospective studies are needed to further assess the impact of follow-up CTA examinations on clinical management as well as to identify the optimal timing and patient selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical management was adjusted in 66% of the entire study population demonstrating the high potential of coronary CTA examinations for therapy evaluation and optimization in CAD patients. Hence, coronary CTA is expected to be increasingly utilized to track CAD progression ( 34 ). In our opinion, prospective studies are needed to further assess the impact of follow-up CTA examinations on clinical management as well as to identify the optimal timing and patient selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts involving the use of carotid and aortic magnetic resonance imaging [ 31 , 32 ], as well as CT angiography [ 33 ], and most recently the use of 3D vascular ultrasound [ 34 ] are also being investigated not only to assess vulnerable plaque risk, but also the effects of different medical therapies on affecting the progression of plaque. It will be of importance to know whether quantification of vulnerable plaque components beyond that of CAC further improves risk assessment.…”
Section: Other Imaging Methods and Risk Assessmentmentioning
confidence: 99%
“…Currently, detection methods for coronary artery inflammation are hampered by lack of specificity (such as serum biomarkers) or limited availability and high cost (18F-fluorodeoxyglucose or 18F-sodium fluoride PET) (Antoniades et al 2020). Coronary Computed Tomography Angiography (CCTA) is a widely used non-invasive diagnostic tool to detect FAI and coronary heart disease (Dahal and Budoff 2019), but it has not been popularized due to the side effects of iodine contrast agent, long examination time and high cost (Mark et al 2010). Moreover, it has been shown that iodine contrast agent will increase the attenuation of pericoronary fat in the case of inflammation, thus affecting the risk prediction ability of PCAT.…”
Section: Introductionmentioning
confidence: 99%